2003
DOI: 10.1021/ol0352963
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Catalytic Phenylation of Ketones with a Constrained Geometry Titanium Catalyst

Abstract: [reaction: see text] The catalytic asymmetric addition of phenyl groups from diphenylzinc to ketones is reported. The catalyst, generated from a dihydroxy bis(sulfonamide) ligand and titanium tetraisopropoxide, gives good to excellent enantioselectivities with a range of substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(35 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…In our initial study on the addition of diphenylzinc to acyclic ketones with ligand 1, we found that enantioselectivities peaked when 0.6 eq of titanium tetraisopropoxide was used (9). Using 1.6 eq of diphenylzinc, 0.6 eq of titanium tetraisopropoxide, 10 mol % ligand 1, and a toluene/hexane solvent system, reactions reached completion at room temperature (RT) after 6-24 h (Eq.…”
mentioning
confidence: 99%
“…In our initial study on the addition of diphenylzinc to acyclic ketones with ligand 1, we found that enantioselectivities peaked when 0.6 eq of titanium tetraisopropoxide was used (9). Using 1.6 eq of diphenylzinc, 0.6 eq of titanium tetraisopropoxide, 10 mol % ligand 1, and a toluene/hexane solvent system, reactions reached completion at room temperature (RT) after 6-24 h (Eq.…”
mentioning
confidence: 99%
“…In the study by Walsh and a co-worker using 10 mol% titanium catalyst of 2, ZnPh 2 additions to 5 aromatic, 2 a,b-unsaturated, and 2 aliphatic ketones were conducted at room temperature for reaction times of 6-24 h, affording tertiary alcohols in good to excellent enantioselectivities for aromatic and a,b-unsaturated ketones (88-96% ee) and for aliphatic ketones in 75 and 87% ee. [19] In the study by Yus et al, a titanium catalyst of 5 mol% 2 was employed at 25 8C for 24 h on 4 examples of ZnPh 2 additions to aromatic ketones, furnishing the desired products in enantioselectivities of 80 to 96% ee. [22,23] They also demonstrated addition reactions of arylzinc reagents which were generated from heating arylboronic with ZnEt 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[17] Walsh and co-workers synthesized trans-1,2-bis(hydroxycamphorsulfonylamino)cyclohexane (2), [18] and the titanium complex of 10 mol% 2 has been demonstrated to be an excellent catalyst in asymmetric ZnPh 2 additions to ketones with enantioselectivities up to 96% ee. [19] Later, the titanium complex of ligand 2 was established to catalyze phenyl additions to a,b-unsaturated ketones to give products in good to excellent enantioselectivities. [20] In contrast, the titanium catalytic system of 3 was reported to give tertiary alcohols in lower yields and lower enantioselectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Acidic treatment of (5) followed by stirring of the intermediate glycol (6) with K 2 CO 3 in MeOH for 20 min at room temperature afforded successfully an epoxy-aldehyde (17) in 71% yield. Reduction of the epoxy-aldehyde (17) with NaBH 4 furnished in a high yield an epoxy-alcohol (18), which was led to the corresponding TBDPS-ether (16) (Chart 4).…”
Section: Resultsmentioning
confidence: 99%
“…1) Chiral tertiary alcohol derivatives as building blocks for the synthesis of such bioactive compounds have generally been prepared synthetically by biological and chemical methods including kinetic resolution of racemates, [2][3][4] enantioselective oxygenation of 1,1-disubstituted olefins or substituted aromatics, [5][6][7][8][9][10][11][12] desymmetrization of prochiral tertiary alcohols, [13][14][15] enantioselective alkylation of ketones, [16][17][18][19][20][21][22][23] and asymmetric alkylation of chiral secondary carbinol carbon with memory of chirality. [24][25][26][27] High levels of chiral induction (Ͼ95% ee), however, have been hardly attained by these methods.…”
mentioning
confidence: 99%